Proyeksi beban diabetes melitus di Indonesia tahun 2025–2030 dengan mempertimbangkan faktor risiko obesitas - Desi Desi; Junita Maja Pertiwi; Heriyannis Homenta; Jonesius Eden Manopo; Eva Mariane Mantjoro; Mercy Irda Riantiny Taroreh (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Diabetes Mellitus (DM) is the fastest-growing non-communicable disease in the world and a major health problem in Indonesia. The increase in cases is influenced by risk factors such as obesity and population growth and aging. To date, projections have focused more on prevalence and therefore have not accurately reflected the number of cases as a basis for health service planning. Purpose: To project the number of DM cases in Indonesia from 2025 to 2030, taking into account trends in DM prevalence, obesity, and population growth. Method: This study used a quantitative approach with a descriptive-analytical design and trend projections based on secondary data from the 2007–2018 Basic Health Research, the 2023 Indonesian Health Survey, and the Central Statistics Agency. This study covered residents aged 25–64 years. Researchers conducted descriptive analysis to identify trends, then used Poisson and Negative Binomial regression to test the influence of variables. They also applied linear regression combined with population projections to estimate the number of future cases. Results: The study shows that the number of cases in Indonesia continues to increase over time. The Negative Binomial regression model was the best model because it was able to overcome overdispersion in the Poisson model. Age significantly influenced the number of cases (p=0.04) (p<0.05). Individuals aged 55–64 years have an incidence rate ratio (IRR) of 23.414, indicating that this group experiences an incidence rate of diabetes mellitus that is 23.4 times the incidence rate of the 25–34 years. In contrast, obesity did not show a statistically significant effect (p>0.05). Projections using linear regression also show an increasing trend in the number of cases from 2025 to 2030, reflecting an increase in the future disease burden. Conclusion: The number of cases in Indonesia will continue to increase until 2030 and is significantly influenced by age. Suggestion: Prevention and control efforts are needed, especially for at-risk age groups, and the projection results should be used as a basis for planning future health policies and services. Keywords: Diabetes Mellitus; Obesity; Projection.